Heparan sulfate binding protein treatment ameliorates neuropathology and behavioral abnormalities in mucopolysaccharidosis IIIB mice - Serenella Anzilotti; Melania Scarcella; Mariangela Ciampa; Noemi Di Muraglia; Camilla Anastasio; Chiara Fiorentino; Federica Rossin; Luigi Avallone; Giuseppe Pignataro; Luigi Michele Pavone; Valeria De Pasquale (Cell Death Discovery)
Abstract Mucopolysaccharidosis IIIB (MPS IIIB) is a metabolic neurodegenerative disorder caused by a deficiency of the lysosomal enzyme α-N-acetylglucosaminidase (NAGLU), which is involved in the degradation of heparan sulfate (HS). Affected patients exhibit progressive neurodegeneration, behavioral disturbances, and a shortened lifespan. Currently, there is no effective treatment for MPS IIIB. We have recently developed a new therapeutic strategy based on the use of the HS-binding protein NK1, a spliced variant of hepatocyte growth factor. Here, we demonstrate that treating Naglu −/− mice with recombinant NK1 ameliorates neuropathology by reducing HS storage, lysosomal dysfunction, autophagy imbalance, and neuroinflammation in the cortex and hippocampus of MPS IIIB mouse brains. Furthermore, we found that recombinant NK1 treatment improves cognitive behavior and motor activity in Naglu −/− mice, as assessed using open field, object recognition, and T-maze tests. Our findings suggest that recombinant NK1 is a promising candidate for the treatment of MPS IIIB and other lysosomal storage diseases associated with central nervous system dysfunction.